Cover Picture: Assembly of Large Purely Inorganic Ce‐Stabilized/Bridged Selenotungstates: From Nanoclusters to Layers (Chem. Asian J. 5/2015). Issue 5 (May 2015) - Chen, Wei‐Chao; Qin, Chao; Li, Yang‐Guang; Zang, Hong‐Ying; Shao, Kui‐Zhan; Su, Zhong‐Min; Wang, En‐Bo
<x xml:space="preserve">Abstract</x> Purely inorganic …︁ …︁ polyoxometalate‐based networks containing lanthanide metals are of great interest but remain underdeveloped. In their Full Paper on page 1184 ff., Chao Qin, Zhong‐Min Su et al. report on two large purely inorganic Ce‐containing selenotungstates, a nanocluster Ce6Se6W67 and the first example of a layered Ce6Se10W51 selenotungstate network. Such compounds could serve as ideal model systems for the preparation of novel 3D, purely inorganic porous materials that are stable and insoluble in common organic solvents.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>